设X=1 Y=1
G(1-1)=G(1)G(1)+F(1)+F(1)
因为 F(1)=1
所以 G(0)=G(1)G(1)+2
G(0)=2G(1)+2
又设X=1 Y=0
G(1-0)=G(1)G(0)+F(1)+F(0)
因为 F(0)=0,F(1)=1
所以 G(1)=G(1)G(0)+1
因为 G(0)=2G(1)+2
所以 G(1)=G(1)+2G(1)+2+1
G(1)=3G(1)+2+1
-2G(1)=3
G(1)==-1.5
因为G(0)=2G(1)+2
所以G(0)=2(=-1.5)+2
G(0)=-1
设X=1 Y=-1
G〔1-(-1)〕=G(1)G(-1)+F(1)+F(-1)
因为G(1)=-1.5 F(-1)=-1 F(1)=1
G(2)=(-1.5)G(-1)+0
设X=0 Y=1
G(0-1)=G(0)G(1)+F(0)+F(1)
因为G(0)=-1 G(1)=-1.5 F(0)=0,F(1)=1
G(-1)=(-1)×(-1.5)+1
G(-1)=2.5
因为G(2)=(-1.5)G(-1)+0
所以G(2)=(-1.5)×2.5+0
G(2)=-3.75
G(0)=-1,G(1)=-1.5,G(2)=-3.75